2018
DOI: 10.1165/rcmb.2016-0223oc
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Administration Improves Survival but Worsens Cardiopulmonary Functions in Chlorine-exposed Rats

Abstract: Chlorine is a highly reactive gas that can cause significant injury when inhaled. Unfortunately, its use as a chemical weapon has increased in recent years. Massive chlorine inhalation can cause death within 4 hours of exposure. Survivors usually require hospitalization after massive exposure. No countermeasures are available for massive chlorine exposure and supportive-care measures lack controlled trials. In this work, adult rats were exposed to chlorine gas (LD) in a whole-body exposure chamber, and given o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Of great interest, unanesthetized Br 2 -exposed rats have a significant decrease in heart rate within the first 24 h consistent with Cl 2 inhalation. This finding of bradycardia and respiratory depression in halogen exposure suggests a direct or indirect effect of halogen exposure on the brain regulatory centers and/or sympathetic ganglia, resulting in a reduced ventilatory drive, hypoventilation, and bradycardia (47). Indeed, cardiac ultrastructural damage is consistent with acute adrenergic discharge that, although not manifest acutely, certainly is evident at 7 days when there is unequivocal evidence of LV dilatation and LV systolic and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 87%
“…Of great interest, unanesthetized Br 2 -exposed rats have a significant decrease in heart rate within the first 24 h consistent with Cl 2 inhalation. This finding of bradycardia and respiratory depression in halogen exposure suggests a direct or indirect effect of halogen exposure on the brain regulatory centers and/or sympathetic ganglia, resulting in a reduced ventilatory drive, hypoventilation, and bradycardia (47). Indeed, cardiac ultrastructural damage is consistent with acute adrenergic discharge that, although not manifest acutely, certainly is evident at 7 days when there is unequivocal evidence of LV dilatation and LV systolic and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 87%
“…Okponyia et al (2018) reported severe bradypnea in rats during, and following, whole body high dose chlorine exposure, where respiratory rate rapidly decreased. The authors attribute the changes seen in respiratory parameters, in part, to a direct response of the activation of TRP channels within the respiratory tract resulting in altered breathing pattern (Okponyia et al 2018). Based on the evidence presented, the immediate changes in breathing pattern seen during exposure in our studies could be the result of a combination of activation of nerve fibers, such as pulmonary C-fibers, in the airways causing reflex changes in respiratory parameters as well as activation of specific TRPA1 ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Activation may result in initiation of pain, respiratory depression, secretions, and other protective responses such as bronchoconstriction (Bessac and Jordt 2010). Okponyia et al (2018) reported severe bradypnea in rats during, and following, whole body high dose chlorine exposure, where respiratory rate rapidly decreased. The authors attribute the changes seen in respiratory parameters, in part, to a direct response of the activation of TRP channels within the respiratory tract resulting in altered breathing pattern (Okponyia et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work presented in this issue of the Journal by Okponyia and colleagues (pp. 107-116) was designed specifically to address that question (6).…”
mentioning
confidence: 99%